1991
DOI: 10.1152/ajpregu.1991.261.4.r1028
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and oxytocin secretion in chronically hyposmolar rats

Abstract: Neurohypophysial secretion of vasopressin (AVP) and oxytocin (OT) was studied in rats maintained under hyposmolar conditions for 10-24 days. Graded intravenous infusions of hypertonic saline solutions had no consistent effect on plasma AVP and OT levels until plasma sodium concentration ([Na+]) exceeded 130 mM, after which levels of both hormones increased as an exponential function of plasma [Na+]. Detectable increases in plasma AVP and OT began at significantly lower plasma [Na+] in hyposmolar rats than in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…In mammals, the secretion of vasopressin, the antidiuretic hormone, is enhanced by hyperosmolality and reduced by hypotonicity of the blood (Striker and Verbalis, 1986;Verbalis and Dohanics, 1991). Oxytocin, in turn, is well known for its role in promoting uterine contractions (Summerlee, 1981) and milk ejection (Wakerley and Lincoln, 1973).…”
Section: Abstract: Galanin; Supraoptic Nucleus; Vasopressin; Oxytocimentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, the secretion of vasopressin, the antidiuretic hormone, is enhanced by hyperosmolality and reduced by hypotonicity of the blood (Striker and Verbalis, 1986;Verbalis and Dohanics, 1991). Oxytocin, in turn, is well known for its role in promoting uterine contractions (Summerlee, 1981) and milk ejection (Wakerley and Lincoln, 1973).…”
Section: Abstract: Galanin; Supraoptic Nucleus; Vasopressin; Oxytocimentioning
confidence: 99%
“…Oxytocin, in turn, is well known for its role in promoting uterine contractions (Summerlee, 1981) and milk ejection (Wakerley and Lincoln, 1973). In the rat, however, oxytocin is also potently natriuretic , and its release is osmotically regulated in a manner analogous to that of vasopressin (Striker and Verbalis, 1986;Verbalis and Dohanics, 1991). Neurohypophysial hormone release, therefore, plays a central role in systemic osmoregulation.…”
Section: Abstract: Galanin; Supraoptic Nucleus; Vasopressin; Oxytocimentioning
confidence: 99%
“…injection of 256 pmol AM or saline vehicle, and then given access to the sucrose solution for 8 h as before. Experimental intakes were compared with sucrose intake on the day prior to experimentation Preinjection intake (ml) Postinjection intake (ml) , Verbalis & Dohanics 1991, Blackburn et al 1993. A similar experiment to the hypertonic saline studies was conducted substituting hypertonic mannitol for saline.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, i.v. infusion of hypertonic saline or chronic salt loading in rats led to increased plasma OT levels (Balment et al 1980, Vant Tol et al 1987, Verbalis & Dohanics 1991, Verbalis et al 1995. Not only does sodium stimulate OT production and release, but also OT acting within CNS sites inhibits further NaCl consumption, providing a negative feedback loop to maintain sodium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hyponatremia, which inhibits secretory activity in the MCNs (Verbalis et al, 1986;Robinson et al, 1990;Verbalis and Dohanics, 1991), also produces an enhanced degeneration of the MCNs after axonal injury in the HNS (Dohanics et al, 1996). Because both of these treatments lead to decreased functional activity of the MCNs, it was suggested that there is a neuroprotective role of functional activity in the HNS after axonal injury (Herman et al, 1987;Dohanics et al, 1996).…”
Section: Introductionmentioning
confidence: 99%